Causes of bullying and strategies for prevention in pesantren: A holistic approach to creating an inclusive environment - Azizah, Nur Ramadhani Risti; Sa'adah, Nurus (STAI Auliaurrasyidin Tembilahan, 2025)
This study examines the factors contributing to bullying in Indonesian Islamic boarding schools (pesantren) and proposes solutions to address the issue. Using a qualitative approach and thematic analysis, data were collected through in-depth interviews, observations, and document studies involving pesantren administrators, teachers, senior and junior students, and parents of Pondok Pesantren As-Sa'idiyyah 2, Jombang. Findings reveal that despite pesantren promoting high moral values, bullying persists in verbal, physical, and emotional forms. Key contributing factors include (1) rigid social hierarchy, (2) inadequate supervision, (3) masculinity-driven culture fostering aggression, (4) lack of education on diversity and empathy, (5) power imbalances between teachers and students, and (6) limited awareness of bullying’s long-term impact. To address this, the study recommends adopting a child-friendly boarding school model that prioritizes students’ psychological and social well-being. Proposed solutions include holistic education on justice, empathy, and diversity, along with clear, consistent anti-bullying policies. Strengthening communication among teachers, administrators, students, and parents is also essential. This study contributes to developing more inclusive and empathetic educational policies to create a bullying-free pesantren environment.